The prevalence of elder abuse and risk factors: a cross-sectional study of community older adults - Reza Nemati-Vakilabad; Zahra Khalili; Leila Ghanbari-Afra; Alireza Mirzaei (BMC Geriatrics, 2023)
Abstract Background The old people population is increasing worldwide. Along with their increasing population, an increase in elder abuse cases is predicted. Elder abuse is a neglected problem, and many cases go unreported. This study was conducted to identify types of elder abuse and examine associated risk factors. Methods This cross-sectional analytical study was conducted on 500 older people in Ardabil (northwestern Iran). Data was collected over three months, from June to September 2020. Data was collected using a demographic information form and the Domestic Elder Abuse questionnaire. The data were analyzed using SPSS software (version 22). Logistic regression was used to identify factors related to elder abuse. Results The results showed that out of the 500 participants, 258 (51.6%) were male, and 242 (48.2%) were female. Among the 500 participants, 377 individuals (75/4%) reported experiencing at least one type of abuse in the past year. The highest rate of elder abuse was observed for emotional neglect (47.2%) and psychological abuse (40.8%), while the lowest rate was measured for rejection (15.4%) and physical abuse (12.4%). The results indicated that elder abuse was significantly associated with chronic illness (OR = 0.601, 95% CI: 0.391–0.922) and having 1–4 children (OR = 1.275, 95% CI: 1.137–1.430). Conclusion Considering the high level of elder abuse and its dangerous effects on the quality of life for older people, it is essential to develop appropriate programs to increase awareness among older people and their families.